Effect of Concept Mapping Teaching Strategy on Students’ Misconceptions about Chemical Bonding in Rivers State - Etokeren, Inibehe Sunday; ABOSEDE, Olufunso Olumide, (IJCER (International Journal of Chemistry Education Research), 2022)
This study examined the effect of concept mapping teaching strategy on Senior Secondary Students’ misconceptions about chemical bonding in Rivers State. Mixed method design, specifically, exploratory mixed method design was adopted. The sample comprised 174 SS2 Students. The instruments were Chemical Bonding Misconceptions Diagnostic Test and Interview Schedule validated by two Science Education Lecturers. The reliability coefficient of 0.87 for the Chemical Bonding Misconceptions Diagnostic Test was determined by test-retest method using Pearson Product Moment Correlation Coefficient formula. Careful piloting of the interview schedule was carried out, and the use of scientific terms as well as discussions were avoided to ensure reliability of the interview schedule. Research questions were answered using percentage and hypotheses tested at 0.05 level of significance using Analysis of Covariance. Findings of the study revealed a remarkable reduction in the high extents of students’ misconceptions about chemical bonding on the use of concept mapping strategy while negligible reduction was found with lecture teaching method. Also, statistically significant difference in the misconceptions of students taught with concept mapping strategy and those with lecture method was found. This suggests that students’ misconceptions about chemical bonding were corrected on application of concept mapping strategy. There was gender related difference in misconceptions of students taught chemical bonding using concept mapping strategy. It was recommended among others that; teachers should embrace the use of conceptual change strategies such as concept mapping in teaching chemical bonding and other abstract concepts in chemistry. Also, students’ misconceptions should be identified at the beginning of the lesson to facilitate correction. Keywords: misconceptions, concept mapping, chemical bonding, and teaching strategy